The Effect of Respiratory Exercise Therapy on Improving Lung Function in Tuberculosis Patients: A Systematic Review - Tenriola, Andi; Aulia Khumaerah; Dewi Hestiani K (Lembaga Penelitian dan Pengabdian Masyarakat, Stikes Panrita Husada Bulukumba, 2025)
Tuberculosis (TB) remains a major global health concern with a high burden of disease, particularly in developing countries. Pulmonary TB infection often leads to permanent lung damage and impaired pulmonary function even after completion of standard treatment. Pulmonary rehabilitation, especially through breathing exercises, is considered a simple, low-cost, and promising intervention to improve lung function and quality of life in TB patients. However, existing evidence has reported inconsistent results. To evaluate the effects of breathing exercise therapy on pulmonary function in patients with tuberculosis through a systematic review based on PRISMA 2020 guidelines. A comprehensive literature search was conducted in PubMed, Scopus, ProQuest, ScienceDirect, and Google Scholar using the keywords “tuberculosis,” “breathing exercise,” “respiratory physiotherapy,” and “lung function.” The search was limited to articles published between 2010 and 2025. Eligible studies included primary research with randomized controlled trials, quasi-experimental, or cohort designs that investigated breathing exercises in TB patients with pulmonary function outcomes. Article selection followed the PRISMA flow diagram. Data extracted included authors, year, study design, sample size, intervention type, duration, frequency, and outcomes. Study quality was assessed using the JBI Critical Appraisal Tools and the Cochrane Risk of Bias Tool. Out of 1,235 articles identified, 7 studies met the inclusion criteria. Interventions examined included pursed-lip breathing, diaphragmatic breathing, incentive spirometry, and structured pulmonary rehabilitation programs. Most studies reported significant improvements in pulmonary function parameters (FEV1, FVC, FEV1/FVC), as well as enhanced exercise capacity and quality of life. Interventions lasting at least 6–12 weeks with a frequency of ≥3 sessions per week produced more consistent results compared to short-term interventions. Variations in findings were observed across study designs, sample sizes, and types of breathing exercise. Breathing exercise therapy is effective in improving lung function, exercise tolerance, and quality of life in patients with TB and post-TB lung disease. This intervention should be considered as part of pulmonary rehabilitation and long-term TB management strategies. Further large-scale randomized controlled trials with standardized protocols are needed to strengthen evidence-based physiotherapy recommendations.